Systemtherapie prognostisch ungünstiger CUP-Syndrome: Adeno- und undifferenzierte Karzinome - Bochtler, Tilmann; Krämer, Alwin (Der Onkologe, 2017)
BackgroundCancer of unknown primary (CUP) designates cancer with histologically confirmed metastases but without an identifiable primary site in spite of a thorough diagnostic work-up. Approximately 2-3% of all cancers fall into the CUP category. Histologically, adenocarcinomas and undifferentiated carcinomas are the prevailing entities.ResultsPatients with CUP who do not fall into one of the well-defined favorable subsets and who are not eligible for local treatment by surgery or radiotherapy should be treated with empirical chemotherapy, even though evidence from clinical trials is scarce for this rare and heterogeneous entity. A combination chemotherapy with a platinum derivative, either carboplatin or cisplatin and a taxane appears to be the most effective. The combination of a platinum compound together with gemcitabine appears to be an alternative choice. Chemotherapy triplets confer excess toxicity without relevant benefits. Currently, it is unclear whether the addition of an antibody to chemotherapy can improve the prognosis. The results of the German PACET-CUP trial, which is testing the addition of the antibody cetuximab to chemotherapy with carboplatin and paclitaxel in a randomized design, are eagerly awaited. Since chemotherapy fails to overcome the typically dismal prognosis of CUP patients with a median overall survival of less than 2 years, novel therapeutic approaches are warranted. High hopes are placed on mutational profiling and subsequent targeted therapy. A comprehensive study based on molecular profiling and molecularly stratified treatment is currently being prepared.ConclusionDisseminated CUP syndromes are commonly treated with chemotherapy. Combination chemotherapies including a platinum compound and either a taxane or gemcitabine are well established. Targeted therapies based on mutational profiling of the tumor tissue are increasingly being introduced into clinical practice.
Gesehen am 14.09.2018